Control interno basado en coso i y su incidencia en la productividad del área operativa de la empresa boncao s.a., periodo 2021-2022 - Lucas Ponce , Evelyn Luisana (2024)
The objective of this research project is to evaluate internal control in the company Boncao S.A. In order to grow and develop in the business environment that develops, the board of directors in search of a solution to the problems presented in the area, which caused economic losses in the periods 2021 and 2022, due to inadequate management in internal control processes, in the use of human and economic resources. For which it was based on the evaluation of internal control and the application of indicators in the operational area to measure compliance with the procedures manual, a questionnaire based on COSO I, the application of a SWOT analysis, for which it was used as types documentary research to review the information, field that helped with the collection of information, descriptive used to represent what happened in the entity, inductive, deductive, statistical and historical-logical research methods, for the selection of appropriate tools in data collection and analysis. The techniques used observation, interview, survey and SWOT analysis, which allowed obtain valid, reliable data to analyze and achieve legitimacy of the development of the results. In this research, the total population was used, because it was finite. In the Results: The level of non-compliance with the procedures manual was known, the level of confidence in 2021 was 60%, classified as moderate, and the risk level was 40%. For the year 2022, the confidence level was 65% classified as moderate and the risk level was 35% classified as low, based on the application of COSO I, also the factors internal and external. The company needs to improve its internal control system, reform and control the implementation of the procedures manual with stricter sections.